ANATOMICAL STRUCTURE OF ASSIMILATIVE ORGANS IN DOMINANT SPECIES OF THE FAMILY CHENOPODIACEAE (AMARANTHACEAE S.L.) (Experimental biology, 2024)
The Chenopodiaceae family is one of the largest and most ancient families in arid regions of the globe. The representatives of this family, being dominants and edificators of many desert plant communities, play a significant role in forming the vegetation cover, particularly the species of the Salsoloideae subfamily.  This study aimed to identify the anatomical structural features of the dominant species of the Chenopodiaceae family growing in arid regions. The study objects are species of the Chenopodiaceae family growing in arid territories of the Kyzylorda region. The study of the anatomical structure of assimilative organs revealed the following types: Cоrispermоid-type, Ventrо-dоrsal type, Kоchiоid-type, Atriplicоid-type, Salsina-type, Shоberia-type, Salsоlоid-type, and Climacоptera-type. The anatomical structure of Atriplex dimorphostegia was clarified. Haloxylon aphyllum was transferred from the Kranz-ventrodorsal type to the Salsoloid type. For the first time, a detailed anatomical structure of the leaves of Salsola sogdiana and Caroxylon nitrarium species was described.
Keywords: Salsoloideae, Suaedoideae, Chenopodioideae, anatomical structure, kranz cells, arid territories, C4 photosynthesis